An exploratory study on competitive intelligence: Managers’ information needs in higher education sector - Oraee, Narges; Sanatjoo, Azam; Ahanchian, Mohammad Reza (Malaysian Journal of Library and Information Science, 2021)
Competitive intelligence is the collection and analysis of information to support strategic decision making for an organisation, as a means to achieve competitive advantages. Identification of information needs is a prerequisite for the subsequent actions and activities in the competitive intelligence process, and, if not done well, optimal intelligence will not be provided. Intending to identify the information needs of university managers in higher education sector, this study addressed the different dimensions of information needs, information sources, and channels used by them. Due to the nature of the subject and research objectives, the research approach was qualitative based on Grounded Theory, an inductive, theory discovery methodology. Twenty-three university managers in Iran were purposively sampled for interviews. It was found that their information needs were mostly about university competitors, university customers and their higher education providers. Their information needs for strategic decisions and actions were about their collaborators in education and information field, effective marketing about product and services, as well as economic, socio-cultural and legal aspects. They need to pay attention to political and economic information in dealing with unexpected topics. Managers obtained information they needed from four types of information sources and channels - human, organisations, open source documents and captured media, and mixed channels. Electronic information sources were considered to be more abundant for them than printed sources. The paper suggests that the findings can contribute to the design, implementation, and development of competitive intelligence information systems that managers and decision-makers are among its major users.